Odpowiedź :
Odpowiedź i szczegółowe wyjaśnienie:
ZADANIE 1:
[tex]a)\ 3^7:3^4=3^{7-4}=3^3=27\\\\b)\ (-5)^8:(-5)^6=(-5)^{8-6}=(-5)^2=5^2=25\\\\c)\ (\frac23)^6:(\frac23)^3=(\frac23)^{6-3}=(\frac23)^3=\frac{8}{27}\\\\d)\ (2\frac13)^5:(2\frac13)^3=(2\frac13)^{5-3}=(2\frac13)^2=(\frac{7}{3})^2=\frac{49}{9}\\\\e)(-1,2)^2:(-1,2)^0=(-1,2)^{2-0}=(-1,2)^2=(1,2)^2=1,44[/tex]
ZADANIE 2.
[tex]a)\ 7^6\cdot7^{12}=7^{6+12}=7^{18}\\\\b)\ 5\cdot5^6\cdot5^0\cdot5^4=5^{1+6+0+4}=5^{11}\\\\c)\ (\frac23)^5\cdot(\frac23)^2\cdot(\frac23)^0=(\frac23)^{5+2+0}=(\frac23)^7\\\\d)\ (2a)^3\cdot(2a)^7=(2a)^{3+7}=(2a)^{10}\\\\e)\ (-12)^4\cdot(-12)^8\cdot(-12)^5=(-12)^{4+8+5}=(-12)^{17}\\\\f)\ (1\frac14)^5\cdot(1\frac14)^7\cdot(1\frac14)^2=(1\frac14)^{5+7+2}=(1\frac14)^{14}[/tex]